Patient satisfaction in urban primary health centres: case of Lucknow and Prayagraj districts in Uttar Pradesh, India - Agarwal, Manoj K.; Mishra, Sunanda (International Journal Of Community Medicine And Public Health, 2022)
Background: Patient satisfaction is one of the expected outcomes of healthcare, as it is closely connected to health-care utilization. It reflects patients’ views on the quality of healthcare and the responsiveness of the healthcare system. There is a strong correlation that exists between patient’s satisfaction and their willingness to seek care at the preferred facility. Methods: A patient exit interview was carried out among 200 patients attending the urban primary health centre (UPHC) in two rationally selected district of Uttar Pradesh. Information regarding services and atmosphere of the UPHC was gathered using a pre-designed questionnaire during September 2019-December 2019. Binominal logistic regression, both simple and multi-variate were conducted to identify the factors which contribute significantly to patient’s satisfaction. Results: Overall we found that 57 percent of the patients were satisfied with the concerned UPHC and factors like examining authority, availability of medicines, waiting time, convenient opening hours, location of the UPHC and availability of waiting area were significantly associated with the patients’ satisfaction. Having found the opening hours convenient and waiting space available were the strongest predictors of patient satisfaction. Conclusions: In conclusion majority of the patient were satisfied, still there is a need to work upon factors like making adequate space available for the patients to wait and modifying the working hours of the UPHC as per the patients need so as to attain the highest level of patient satisfaction.